Defective PITRM1 mitochondrial peptidase is associated with Aβ amyloidotic neurodegeneration - Dario Brunetti; Janniche Torsvik; Cristina Dallabona; Pedro Teixeira; Pawel Sztromwasser; Erika Fernandez‐Vizarra; Raffaele Cerutti; Aurelio Reyes; Carmela Preziuso; Giulia D'Amati; Enrico Baruffini; Paola Goffrini; et al. (EMBO Molecular Medicine)
Abstract Mitochondrial dysfunction and altered proteostasis are central features of neurodegenerative diseases. The pitrilysin metallopeptidase 1 (PITRM1) is a mitochondrial matrix enzyme, which digests oligopeptides, including the mitochondrial targeting sequences that are cleaved from proteins imported across the inner mitochondrial membrane and the mitochondrial fraction of amyloid beta (Aβ). We identified two siblings carrying a homozygous PITRM1 missense mutation (c.548G>A, p.Arg183Gln) associated with an autosomal recessive, slowly progressive syndrome characterised by mental retardation, spinocerebellar ataxia, cognitive decline and psychosis. The pathogenicity of the mutation was tested in vitro, in mutant fibroblasts and skeletal muscle, and in a yeast model. A Pitrm1+/− heterozygous mouse showed progressive ataxia associated with brain degenerative lesions, including accumulation of Aβ‐positive amyloid deposits. Our results show that PITRM1 is responsible for significant Aβ degradation and that impairment of its activity results in Aβ accumulation, thus providing a mechanistic demonstration of the mitochondrial involvement in amyloidotic neurodegeneration.